Zeolites as nanoporous, gas-sensitive materials for in situ monitoring of DeNOx-SCR - Simons, Thomas; Simon, Ulrich (Beilstein Journal of Nanotechnology, 2012)
In a proof-of-concept study we demonstrate in situ reaction monitoring of DeNOx-SCR on proton-conducting zeolites serving as catalyst and gas sensor at the same time. By means of temperature-dependent impedance spectroscopy we found that the thermally induced NH3 desorption in H-form and in Fe-loaded zeolite H-ZSM-5 follow the same process, while a remarkable difference under DeNOx-SCR reaction conditions was found. The Fe-loaded catalyst shows a significantly lower onset temperature, and time-dependent measurements suggest different SCR reaction mechanisms for the two catalysts tested. These results may help in the development of catalysts for the reduction of NOx emissions and ammonia consumption, and provide insight into the elementary catalytic process promoting a full description of the NH3-SCR reaction system.
Keywords: DeNOx-SCR; gas sensing; in situ; impedance spectroscopy; zeolite